Redesigning English Syllabus And Lesson Plan For The First Graders Of Elementary School - Windyaningrum, Shinta; Arini, Restu (LPPM Universitas Mercu Buana Yogyakarta, 2016)
AbstractThe objectives of this research were: 1) to find out the strengths and weaknesses of English syllabus and lesson plan for the first graders used by the teacher in SD Panggang; (2) to explain the process of redesigning English syllabus and lesson plan; (3) to present the result of the implementation of redesigning English syllabus and lesson plan for the first graders of elementary school. This research was conducted by using Research and Development (R&D) method which involved eight phases to redesign syllabus and lesson plan. The instruments were used to collect the data by interviewing, observing classroom, and analyzing syllabus and lesson plan. The subject of this research were 30 students consisting of male and female students. The result of this research showed that English syllabus and lesson plan had the strengths and weaknesses. There were the strengths of syllabus including basic competence, assessments, and learning source. Whereas, the weaknesses of English syllabus, there were learning material, learning activity, indicator, and time allocation. Moreover the strengths of lesson plan covered identity column, standard competence; basic competency, and source of learning. The last was the weaknesses of lesson plan consisting of indicators, learning objectives, learning material, steps of learning, and rubric assessments. Then, the result of implementation for the first graders of elementary school was good. The students were very enthusiastic, happy and fun when they learnt English based on their needs.